The Relationship Between Employee Motivation and Work Discipline to the Nurse of the Mongeudong Public Health Center, Banda Sakti District, Lhokseumawe City - Bukhari; Wawan Supandi (Jurnal Kesehatan Akimal, 2022)
The IOM (United States Institute of Mediciene), in 2000 made a report "To Error is Human, Building to Safer Health System" which states that discipline carries out the work that has been set. The impact of a lack of discipline in work includes a lack of quality in service, while based on a report from New York it was found that 3.7% of unexpected events, 13.6% of them were of low quality. The incidence rate is not estimated with a range of 3.2 to 16.6% in hospitals in various countries, namely Australia, Denmark, England and the United States. Motivation is a desire, need, goal and drive, so it can be concluded that motivation is a condition that can encourage, move or activate and direct and channel a person's behavior that is directed at achieving a goal. Discipline is a force that grows and develops within the worker's body and causes the worker to voluntarily conform to decisions, rules, and high work values ​​and behavior. The research model used in this study is analytic observation, where the research model is cross sectional. The population in this study were all employees of the Mongeudong Public Health Center, Banda Sakti District, Lhokseumawe City, totaling 88 people. The side technique used is Total Sampling. Research instruments and measurement methods; Data collection researchers used a questionnaire that was tested for reliability and validity. By using the Chi Square test method, it was found that the P value = 0.002 <= 0.05, so H0 was rejected, or in other words there was a relationship between work motivation and employee discipline at the Mongeudong Health Center, Banda Sakti District, Lhokseumawe City.